Acromioclavicular Joint Injuries in Sport. Issue 3 (March 2023) - Kelley, Naomi; Tuttle, Matthew; Sylvia, Stephen M.; Dragoo, Jason L.; Khodaee, Morteza
Abstract: Sport-related shoulder injuries, including disruptions to the acromioclavicular joint (ACJ), are common. An ACJ injury is classified by the degree and direction of the clavicle displacement. Although the diagnosis can be made clinically, standard radiographic views are important to determine the severity of the ACJ disruption and assess for concurrent injuries. The majority of ACJ injuries can be managed nonoperatively; however, surgical treatment is indicated in some cases. Long-term outcomes are generally favorable for most ACJ injuries, and athletes generally return to sport without functional limitations. This article provides an in-depth discussion regarding all aspects of ACJ injuries, including clinically relevant anatomy, biomechanics, evaluation, treatment, and complications.